Modeling Human Mortality from All Diseases in the Five Most Populated Countries of the European Union - Dolejs, Josef (Bulletin of mathematical biology, 2017)
Age affects mortality from diseases differently than it affects mortality from external causes, such as accidents. Exclusion of the latter leads to the "all-diseases" category. The age trajectories of mortality from all diseases are studied in the five most populated countries of the EU, and the shape of these 156 age trajectories is investigated in detail. The arithmetic mean of ages where mortality reaches a minimal value is 8.47 years with a 95% confidence interval of [8.08, 8.85] years. Two simple deterministic models fit the age trajectories on the two sides of the mortality minimum. The inverse relationship is valid in all cases prior to this mortality minimum and death rates exactly decreased to three thousandths of its original size during the first 3000 days. After the mortality minimum, the standard Gompertz model fits the data in 63 cases, and the Gompertz model extended by a small quadratic element fits the remaining 93 cases. This analysis indicates that the exponential increase begins before the age of 15 years and that it is overshadowed by non-biological causes. Therefore, the existence of a mechanism switching that would explain the exponential increase in mortality after the age of 35 years is unlikely.
Keywords: dospělí; Female; Infant; Models, Statistical; dítě; předškolní dítě; Mortality; novorozenec; Age Factors; Adult; mladý dospělý; ženské pohlaví; Adolescent; věkové faktory; lidé; Infant, Newborn; statistické modely; Evropská unie; Aged, 80 and over; mortalita; Male; kojenec; Aged; Child, Preschool; Young Adult; European Union; lidé středního věku; Child; senioři nad 80 let; senioři; mužské pohlaví; Middle Aged; mladiství; Humans